Corpus Callosum Microstructural Alterations In Children With Memory Related Learning Disability: A Diffusion Tensor Imaging Study - Abd elhameed, Abeer Maghawry; Mohammad, Shaimaa Abdelsattar; Nashaat, Neveen Hassan; Abdel-Rahman, Amgad Samy; Raouf, Ehab Ragaa Abdol (QJM : An International Journal of Medicine, 2021)
Abstract Purpose The purpose of this study is to assess the corpus callosum microstructural changes in children with memory related learning disability. Methods DTI was performed in 20 patients with memory related learning disabilities (MRLD +) and 22 matched healthy control subjects (MRLD -) aged 7– 13 years. Fractional anisotropy (FA), axial diffusivity, radial diffusivity (RD) and trace were calculated for corpus callosum. Comparison between patients with memory related learning disabilities (MRLD +) and healthy control subjects (MRLD -) was performed. DTI metrics were correlated to clinical digit span backward scores in (MRLD +) group. A pvalue less than .05 was considered significant. Results The corpus callosum showed a highly significant higher FA and lower diffusivity indices in (MRLD +) group compared to the (MRLD -) group (p < 0.001). No significant correlation between the clinical test “digit span backward” scores and DTI metrics of the corpus callosum was found. Conclusion Changes in DTI metrics of corpus callosum in patients with memory related learning disabilities reflects white matter micro-structural changes. Higher FA values and lower diffusivity indices do not necessarily indicate healthier white matter but, can indicate pathology.